The Digital Divide in Accounting Education: Challenges and Solutions - Rojas, Edwar Zabarburu; Rodriguez, Victor Hugo Puican (Journal of Cultural Analysis and Social Change, 2025)
In Amazonas—Peru, accountants face challenges arising from a globalized environment and a competitive labor market. Despite geographic isolation, adapting to emerging technologies is essential to remain competitive. The implementation of advanced accounting software and artificial intelligence tools is crucial, but the lack of access and training in these technologies limits the optimization of accounting processes and remote collaboration. Continuing professional development is vital, and accountants should seek learning opportunities through seminars, workshops and distance learning programs. Investment in continuing education ensures that accounting standards and practices are constantly updated. This research highlights the importance of a multifaceted training strategy that addresses both technical skills and ethical and sustainable competencies, preparing Amazon accountants for current challenges and future opportunities. Using a quantitative approach, the research evaluates the effectiveness of training in emerging technologies, ethics and sustainability, highlighting the need to integrate these competencies to improve labor competitiveness in the region. The results indicate a positive, albeit limited, influence of financial capability on professional competitiveness, suggesting the need for policies and educational programs to strengthen this competency.